Application Research of Distributed UAV Nest Based on Multi-Information Fusion Sensor in the Field of Communication. (23rd August 2022) - Cai, Lin
Abstract : For the long delay in the communication field of the unmanned robot, which seriously affects the accurate evaluation of the operation status of the UAV, this paper introduces the multi-information fusion sensor into the field of distributed UAV nest communication. By using the multi-information fusion sensor to fuse the attitude data information of the UAV flight, the delay of the information obtained in the communication process is reduced. The multi-information fusion sensor needs to fully consider the delay problem in the communication field during the use of the UAV nest. By using the acceleration data information to make up for the shortcomings of the delay, relatively accurate and high-precision UAV motion evaluation results can be obtained. According to the simulation of the UAV using the multi-information fusion sensor during the flight, the method proposed in this paper is verified on the UAV system. After comparing the simulation and test results, it can be seen that the method used in this paper can effectively improve the application efficiency of multi-information fusion sensors in the communication field of distributed UAV nests, and has a high reference value for data information analysis.